2020
DOI: 10.3390/antiox9060546
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic Effects of Melatonin and Omega-3 Are Linked with Protection of Myocardial Cx43 Topology and Suppression of Fibrosis in Catecholamine Stressed Normotensive and Hypertensive Rats

Abstract: Cardiac β-adrenergic overstimulation results in oxidative stress, hypertrophy, ischemia, lesion, and fibrosis rendering the heart vulnerable to malignant arrhythmias. We aimed to explore the anti-arrhythmic efficacy of the anti-oxidative and anti-inflammatory compounds, melatonin, and omega-3, and their mechanisms of actions in normotensive and hypertensive rats exposed to isoproterenol (ISO) induced β-adrenergic overdrive. Eight-month-old, male SHR, and Wistar rats were injected during 7 days with ISO (cumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 77 publications
(143 reference statements)
2
22
0
Order By: Relevance
“… 34 Recently, a study reported that a reduction in fibrosis and upregulation of Cx43 rendered the heart less susceptible to malignant arrhythmias in the isoproterenol model of heart failure. 35 In the present study, we found that CCM partially restored the prolonged QTc interval and ERP, and reduced the susceptibility to ventricular arrhythmia. At the molecular level, CCM reversed downregulation of Kv4.3, KCNQ1, KCNH2 and Cx43 protein expression, which may contribute to attenuation of electrical remodeling in HF.…”
Section: Discussionsupporting
confidence: 65%
“… 34 Recently, a study reported that a reduction in fibrosis and upregulation of Cx43 rendered the heart less susceptible to malignant arrhythmias in the isoproterenol model of heart failure. 35 In the present study, we found that CCM partially restored the prolonged QTc interval and ERP, and reduced the susceptibility to ventricular arrhythmia. At the molecular level, CCM reversed downregulation of Kv4.3, KCNQ1, KCNH2 and Cx43 protein expression, which may contribute to attenuation of electrical remodeling in HF.…”
Section: Discussionsupporting
confidence: 65%
“…Also, melatonin reduces arrhythmias when administered during reperfusion. Specifically, melatonin has shown to have a protective action when administered to isolated hearts of hypertensive rats [ 14 ]. These animals show greater activity of the enzyme NADPH oxidase, which is one of the main systems for generating free radicals, and, therefore, higher levels of oxidative stress, which is involved in the generation of early and delayed afterdepolarizations [ 229 ].…”
Section: Melatonin As a Potential Antiarrhythmic Treatment In Aginmentioning
confidence: 99%
“…Therefore, the potential as an antiarrhythmic to act in the acute scenario is clearly available. However, the evidence is still mainly preclinical [ 14 , 198 , 221 , 229 , 236 ]. In the context of ischemia/reperfusion, simultaneous intravenous and intracoronary administration has been proven to be electrophysiologically safe.…”
Section: Melatonin As a Potential Antiarrhythmic Treatment In Aginmentioning
confidence: 99%
“…Since impulse propagation in the heart is mediated via connexin-formed gap junctional channels and the preservation of connexin topology has anti-arrhythmic effects [78][79][80], the alterations of right atrial and ventricular electrophysical properties suggest a deregulation of connexin expression/function in experimental models of PH. The amount of Cx43 is assessed at different time periods after administration of monocrotaline.…”
Section: Pulmonary Hypertension: Connexins In Right Ventricular Hypertrophy and Failurementioning
confidence: 99%